The Principles and Structure of the Islamic Financial System in the Light of Solutions Practiced in the Western World - Karaś, Piotr; Kutrzeba, Tomasz (Krakow Review of Economics and Management/Zeszyty Naukowe Uniwersytetu Ekonomicznego w Krakowie, 2015)
In the subject literature one will encounter the point of view that the recent global financial crisis marks the end of an era in contemporary Western finance. In searching for new ways of developing financial systems, the question can be asked: What can be learnt from Islamic finance? The aim of this article is to try to answer this question by examining the principles of Islamic finance and the construction of the Islamic financial system. We find that, despite existing similarities, the main difference between Islamic finance and the European and American financial systems is that the former is founded on the religious law of Sharia, while, the common standard of Western countries is to maintain separation between church and state. There are also differences in the perception of interest and risk, which make the Islamic financial system complementary to, rather than a substitute for, Western financial systems.